Theoretical and experimental study of braid pattern in mandrels with arbitrary cross-sections. (December 2018) - Hajrasouliha, Jalil; Nedoushan, Reza Jafari; Sheikhzadeh, Mohammad; Na, Wonjin; Yu, Woong-Ryeol
Braid angle is a key factor associated with the mechanical properties of braided composites, so accurate prediction of this angle is of vital importance for the design and manufacture of braided preforms. This paper presents a theoretical model for the prediction of braid angle at any point of a mandrel with constant arbitrary cross-section by taking into account the kinematic parameters of circular braiding machine. The proposed theoretical model pays particular attention to two parameters that strongly affect the braid angle, namely the position of fell point on the mandrel's surface and the yarn length between this point and the carrier. Both of these parameters undergo continuous change during braiding and thus should be calculated on a point-to-point basis. The model was validated by a series of braiding experiments conducted, using a circular braiding machine, on mandrels with circular, elliptical, and oval cross-sections and then determining the resulting braid angles over the mandrel's surface by an image processing method. The experimental results showed the high accuracy of the proposed theoretical model in predicting the braid angle for mandrels with constant arbitrary cross-section. Thus, the proposed model can contribute to faster and more accurate design and manufacture of braided composite preforms.